2017
DOI: 10.12659/msm.905591
|View full text |Cite
|
Sign up to set email alerts
|

A Nonrandom Sample of 55 Sexual Abuse Cases in Sivas

Abstract: BackgroundSexual abuse in childhood is a significant public health problem because of the destructive results both to the individual and to the community. The aim of this study was to examine the sociodemographic characteristics of children who were victims of sexual abuse, the relationship of the victim and abuser, and the findings of sexual abuse.Material/MethodsAn examination was made of the results of forensic medicine and psychiatric evaluations of child victims of sexual abuse. The sociodemographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…The literature reports that 15% of the cases of sexual abuse are perpetrated by more than one aggressor. 33 The results point out that violence is a health problem for women since childhood, the prevalence of violence in females indicated an intergenerational phenomenon, since women are the greatest victims of abuse throughout life. Characteristics of violence against children in Porto Alegre Dornelles TM, Macedo ABT, Antoniolli L, Vega EAU, Damaceno AN, Souza SBC Girls presented an association in relation to the aggressor being under the influence of alcohol during the violence episode when compared to boys.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports that 15% of the cases of sexual abuse are perpetrated by more than one aggressor. 33 The results point out that violence is a health problem for women since childhood, the prevalence of violence in females indicated an intergenerational phenomenon, since women are the greatest victims of abuse throughout life. Characteristics of violence against children in Porto Alegre Dornelles TM, Macedo ABT, Antoniolli L, Vega EAU, Damaceno AN, Souza SBC Girls presented an association in relation to the aggressor being under the influence of alcohol during the violence episode when compared to boys.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have considered that cases of child sexual abuse remain hidden because of the effects of regional sociocultural factors and fear and hesitation about the legal process [25,26]. “Sexual grooming,” which has become synonymous with child sexual abuse, promotes initial cooperation from the victim and increases the likelihood of future sexual contact [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Aydın et al consisting of 1002 cases in 2014, it was stated that almost half of the cases (47.9%) were abused in the home environment (Aydin B, 2015). In a study covering the years 2013-2016 in Sivas province; It was reported that 52.7% of the incident took place in the home environment (Butun et al, 2017). Thus, it is seen that most of the abuses take place in areas known as safe areas.…”
Section: Discussionmentioning
confidence: 99%